PENINGKATAN KEMAMPUAN MENYIMAK LAPORAN PERJALANAN DENGAN METODE INKUIRI MENGGUNAKAN MEDIA VIDEO - Heryansyah, Heryansyah (Jurnal Edukasi Khatulistiwa : Pembelajaran Bahasa dan Sastra Indonesia, 2018)
This study aimed to describe the increase in the ability to listen to a trip report by inquiry method using video media in class VIII B SMPN 2 Segedong Pontianak District in Academic Year 2013/2014.This research method is descriptive with this kind of research is classroom action research conducted through three cycles. Each cycle consists of planning, action, observation, and reflection.The study concluded that the inquiry method with video media effectively used in improving listening skills a trip report on class VIII B SMP Negeri 2 Segedong Pontianak district academic year 2013/2014.